2008
DOI: 10.1007/s11427-008-0103-z
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic hyperspectral imaging studies of normal and diabetic retina of rats

Abstract: A microscopic hyperspectral imager was developed based on the microscopic technology and the spectral imaging technology. Some microscopic hyperspectral images of retina sections of the normal, the diabetic, and the treated rats were collected by the new imager. Single-band images and pseudo-color images of each group were obtained and the typical transmittance spectrums were extracted. The results showed that the transmittance of outer nuclear layer cells of the diabetic group was generally higher than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…All cited ex vivo microscopy techniques are designed in transmittance mode (Fig. 1B), that is, detectors capture light transmitted through the retina, 27,29,[43][44][45] except for those who used an autofluorescent reflectance mode to study the retinal pigment epithelium (RPE) and inherent fluorophores (as discussed elsewhere in this article). 33,46,47 For in vivo imaging, reflectance mode ( Fig.…”
Section: Hsi Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…All cited ex vivo microscopy techniques are designed in transmittance mode (Fig. 1B), that is, detectors capture light transmitted through the retina, 27,29,[43][44][45] except for those who used an autofluorescent reflectance mode to study the retinal pigment epithelium (RPE) and inherent fluorophores (as discussed elsewhere in this article). 33,46,47 For in vivo imaging, reflectance mode ( Fig.…”
Section: Hsi Techniquesmentioning
confidence: 99%
“…1, B1). [43][44][45] As can be remarked in Table 1, most set-ups that extend their spectrum toward the visible and nearinfrared spectrum (ca. 400-1100 nm) belong to this category.…”
Section: Dispersive Prisms and Gratingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the use of hyperspectral (reflectance) imaging has gained interest in the analysis of microscopic structures, including microbes, tissues and associated constituents (Schultz et al , 2001; Demos et al , 2005; Demos, 2007; Haaland et al , 2007; Li et al , 2007). A review of recent literature has shown diverse application of short‐ and long‐wave microspectroscopy for the study of bacteria, cancer cells, human tissue morphology and general cellular structural analysis, but not for differentiating viable from non‐viable endospores.…”
Section: Introductionmentioning
confidence: 99%